Mixtures of hibiscus sabdariffa stems and roots for anthocyanin synthesis - Nadhila Anatie, Abdul Rahim (2014)
The mixture of H.sabdariffa stems and roots were extracted to get anthocyanin. H.Sabdariffa plant grows seriously in a warm countries including Malaysia. This plant is usually grown for its calyces and flowers which are mainly used for anthocyanin synthesis. Anthocyanin can also be synthesized from other parts of H.Sabdariffa like stems and leaves. The stems of anthocyanin were discarded without any value added product. Thus, this work was done to use the stems and roots mixture for anthocyanin. Besides that, the variations of temperature, time and ethanol-water ratio on the anthocyanin yield were investigated. The anthocyanin was extracted from H.Sabdariffa stems and roots waste using ultrasound technique with ethanol-water as solvent. The anthocyanin yield was analysed using High Performance Chromatography (HPLC). The condition where it gave the highest yield of anthocyanin was at contact time of 30 minutes, temperature of 50oC and 70:30 of ethanol water solvent. Extraction of anthocyanin from roselle approved the second order kinetic yielding good R2 values of 0.9882 and k values 0.0306